TASCI—transcutaneous tibial nerve stimulation in patients with acute spinal cord injury to prevent neurogenic detrusor overactivity: protocol for a nationwide, randomised, sham-controlled, double-blind clinical trial. Issue 8 (13th August 2020) - Birkhäuser, Veronika; Liechti, Martina D; Anderson, Collene E; Bachmann, Lucas M; Baumann, Sarah; Baumberger, Michael; Birder, Lori A; Botter, Sander M; Büeler, Silvan; Cruz, Célia D; David, Gergely; Freund, Patrick; et al.
Abstract : Introduction: Neurogenic lower urinary tract dysfunction (NLUTD), including neurogenic detrusor overactivity (NDO) and detrusor sphincter dyssynergia, is one of the most frequent and devastating sequelae of spinal cord injury (SCI), as it can lead to urinary incontinence and secondary damage such as renal failure. Transcutaneous tibial nerve stimulation (TTNS) is a promising, non-invasive neuromodulatory intervention that may prevent the emergence of the C-fibre evoked bladder reflexes that are thought to cause NDO. This paper presents the protocol for TTNS in acute SCI (TASCI), which will evaluate the efficacy of TTNS in preventing NDO. Furthermore, TASCI will provide insight into the mechanisms underlying TTNS, and the course of NLUTD development after SCI. Methods and analysis: TASCI is a nationwide, randomised, sham-controlled, double-blind clinical trial, conducted at all four SCI centres in Switzerland. The longitudinal design includes a baseline assessment period 5–39 days after acute SCI and follow-up assessments occurring 3, 6 and 12 months after SCI. A planned 114 participants will be randomised into verum or sham TTNS groups (1:1 ratio), stratified on study centre and lower extremity motor score. TTNS is performed for 30 min/day, 5 days/week, for 6–9 weeks starting within 40 days after SCI. The primary outcome is the occurrence of NDO jeopardising the upper urinary tract at 1 year after SCI, assessed by urodynamic investigation. Secondary outcome measures assess bladder and bowel function and symptoms, sexual function, neurological structure and function, functional independence, quality of life, as well as changes in biomarkers in the urine, blood, stool and bladder tissue. Safety of TTNS is the tertiary outcome. Ethics and dissemination: TASCI is approved by the Swiss Ethics Committee for Northwest/Central Switzerland, the Swiss Ethics Committee Vaud and the Swiss Ethics Committee Zürich (#2019-00074). Findings will be disseminated through peer-reviewed publications. Trial registration number: NCT03965299 .